Positive Parenting Psychoeducation to Reduce Parenting Stress in Young Mothers - Tenia Kurniawati (Journal of Universal Community Empowerment Provision, 2026)
Parenting stress is a significant mental health concern among young mothers, especially in vulnerable settings such as Tambrauw Regency, Southwest Papua, where early marriage, low education, poverty, and displacement are prevalent. These challenges increase the risk of maladaptive parenting practices, including verbal, emotional, and physical violence toward children. This study aimed to implement a positive parenting psychoeducation program to reduce parenting stress among young mothers in the PAUD Permata Fef Parents Association. The program was designed based on Bronfenbrenner’s ecological systems theory and delivered over two days using lectures, discussions, role-play, games, and workshops in group and individual formats. A one-group pretest–posttest design was employed with 10 participants aged 17–30 years, most of whom married between 13–18 years old and had low educational backgrounds. Data were analyzed using a paired samples t-test. Results showed a significant difference between pretest (M = 78.70; SD = 7.26) and posttest scores (M = 74.80; SD = 6.76), t(9) = 10.301, p <.001, with a large effect size (Cohen’s d ≈ 3.26). The 3.9-point decrease was interpreted as a post-intervention dip, reflecting increased self-awareness rather than program failure. Participants became more realistic in evaluating their parenting practices after gaining insights. Qualitative observations indicated that the program fostered emotional awareness, social support, and practical skills such as cognitive restructuring, positive communication, emotional regulation, and mindful parenting. The findings suggest that positive parenting psychoeducation is a promising intervention, although follow-up sessions are needed to assess long-term behavioral changes.